2011
DOI: 10.1159/000327517
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Usefulness of CEA, CA19-9, and CYFRA 21-1 as Tumor Markers for Urothelial Bladder Carcinoma

Abstract: Objective: To evaluate the usefulness of measuring serum CEA, CA19-9, and CYFRA 21-1 levels for the diagnosis and monitoring of bladder cancer. Materials and Methods: Serum levels of CEA, CA19-9, and CYFRA 21-1 were measured in 85 patients with bladder cancer. The absolute level of each marker and the positive rate were compared with the clinical stage and histological grade of the tumor. Changes of the markers were assessed in patients with or without disease progression, and the correlations between survival… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 18 publications
0
21
0
Order By: Relevance
“…The percentage of rise in CA 19-9 level in patients with metastatic disease (75.0%) was significantly higher than in patients without metastasis (18.1%) (p value 0.001*) (Hegele et al, 2010). CA 19-9 level was also found to be increased in high-grade tumors (66.6%) as compared with low-grade tumors (22.2%) (p value 0.001*) (Washino et al, 2011). Therefore, even though no serological tumor marker has so far been amply sensitive and specific to be used in screening for transitional cell carcinoma, elevated pre-operative levels of carbohydrate antigen (CA) 19-9 correlate with advances stages of disease and a poorer clinical outcome.…”
Section: Discussionmentioning
confidence: 87%
“…The percentage of rise in CA 19-9 level in patients with metastatic disease (75.0%) was significantly higher than in patients without metastasis (18.1%) (p value 0.001*) (Hegele et al, 2010). CA 19-9 level was also found to be increased in high-grade tumors (66.6%) as compared with low-grade tumors (22.2%) (p value 0.001*) (Washino et al, 2011). Therefore, even though no serological tumor marker has so far been amply sensitive and specific to be used in screening for transitional cell carcinoma, elevated pre-operative levels of carbohydrate antigen (CA) 19-9 correlate with advances stages of disease and a poorer clinical outcome.…”
Section: Discussionmentioning
confidence: 87%
“…For example, recent study showed that loss of canal of Hering marked with K19 staining appeared in the early stage of primary biliary cirrhosis (PBC), and this finding may provide support to clinical diagnosis of PBC [51]. Further, K19 is also often expressed in a variety of human cancers, such as urothelial bladder carcinoma, advanced thyroid cancer and hepatocellular carcinoma (HCC) [10,[44][45]52]. Specifically, in the subtype of HCC which characterized with expression of K19, it is histologically poorly differentiated and exhibit aggressive tumour activity.…”
Section: Function Of Keratinsmentioning
confidence: 96%
“…the lining of gastroenteropancreatic and hepatobiliary tracts) are among tissues with the highest K19 expression (Table 2) [10,[44][45]. Of note, K19 expression is restricted to the biliary system in adult liver under physiological condition, and therefore, K19 represents as an established marker for cholangiocytes [46].…”
Section: Function Of Keratinsmentioning
confidence: 99%
See 1 more Smart Citation
“…According to the inclusion criteria, 3 studies (Sánchez-Carbayo et al, 1999;Andreadis et al, 2005;Washino et al, 2011) met the inclusion criteria and were included in the metaanalysis. The flow chart of study selection is shown in Figure 1.…”
Section: Characteristics Of Studies Includedmentioning
confidence: 99%